The Disordered Vaginal Microbiota Is a Potential Indicator for a Higher Failure of in vitro Fertilization - Kong, Yao; Liu, Zhaoxia; Shang, Qingyao; Gao, Yuan; Li, Xia; Zheng, Cihua; Deng, Xiaorong; Chen, Tingtao (Frontiers in Medicine, 2020)
Infertility is one of the most common reproductive system diseases, and no effective method is available for its treatment. Although in vitro fertilization (IVF) has been widely used to enhance the clinical pregnancy outcome of infertility, the unsatisfied pregnancy rate with unknown reasons is obtained. To identify the possible cause of IVF failure, 555 patients were enrolled in the present study to determine their relevant clinical characteristics and vaginal microbiota. Our results indicated that the age and endometrium thickness significantly affected the pregnancy success rate of pregnant patients (P group) and non-pregnant patients (NP group) receiving IVF, and high values of luteinizing hormone, estrogen and progesterone were observed from P group. Furthermore, the Partial Least Squares Discriminant Analysis (PLS-DA) indicated a different microbial composition in P group and NP group, and a higher microbial abundance had been identified in non-pregnant patients compared with pregnant patients. At phylum level, a higher abundance of Firmicutes and Proteobacteria, and a lower abundance of Actinobacteria, Fusobacteria, and Bacteroidetes were obtained in pregnant patients compared with non-pregnant patients. At genus level, a lower abundance of the probiotic Lactobacillus, and higher abundance of pathogens Gardnerella and Prevotella were identified from non-pregnant patients. Therefore, the disordered microbiota, characterizing by the reduction of probiotics and overgrowth of pathogens in non-pregnant patients, may be used as a potential indicator for a higher IVF failure rate.